THE EFFECTIVENESS OF DISCOVERY LEARNING MODEL TO INCREAS STUDENTS' MATHEMATICAL UNDERSTANDING ABILITY - Sartono; Zainuddin Zainuddin; Sahrun Nisa; Serly Safitri (Jurnal Cakrawala Pendas, 2023)
Mathematics is one of the mandatory subjects that every student needs to understand. In mathematics, fractions are one of the materials that students consider difficult. Several studies have found that students cannot understand the concept of fractions well. Students' ability to understand mathematics is called mathematical comprehension ability. This ability is a basic ability in mastering mathematics. One model that is considered capable of improving students' mathematical abilities is the discovery learning model. This research aims to reveal the effectiveness of the discovery learning model in improving coastal students' mathematical understanding. This research is quantitative research using a pre-experiment design which was carried out at SDN 111 Buton in the odd semester of the 2022/2023 academic year. Based on the results of data processing and analysis, researchers found that the discovery learning model can improve coastal students' mathematical understanding abilities. These findings are evidence that this learning model can be used to improve coastal students' mathematical understanding abilities. Therefore, this model can be an alternative in improving students' mathematical abilities. Matematika sebagai salah satu mata pelajaran wajib yang perlu dipahami oleh setiap siswa. Dalam matematika, pecahan merupakan salah satu materi yang dianggap sulit oleh siswa. Beberapa penelitian menemukan bahwa siswa tidak dapat memahami konsep pecahan dengan baik. Kemampuan siswa dalam memahami matematika disebut dengan kemampuan pemahaman matematika. Kemampuan ini merupakan kemampuan dasar dalam menguasai matematika. Salah satu model yang dianggap mampu meningkatkan kemampuan matematika siswa adalah model discovery learning. Penelitian ini bertujuan untuk mengungkap keefektifan model discovery learning dalam meningkatkan coastal students' mathematical understanding. Penelitian ini merupakan penelitian kuantitatif yang menggunakan desain pre-experiment yang dilaksanakan di SDN 111 Buton pada semester ganjil tahun ajaran 2022/2023. Berdasarkan hasil pengolahan dan analisis data, peneliti menemukan bahwa model discovery learning dapat meningkatkan kemampuan pemahaman matematis siswa pesisir. Temuan tersebut menjadi bukti bahwa model pembelajaran ini dapat digunakan untuk meningkatkan kemampuan pemahaman matematis siswa pesisir. Oleh karena itu, model ini dapat menjadi salah satu alternatif di dalam meningkatkan kemampuan matematis peserta didik.